PROFIL SELF CONFIDENCE SISWA MTS AL BIDAYAH - Neng Eliza Purnamasari; Ecep Supriatna; Ardian Renata Manuardi (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
Self-Confidence is an individual who can work effectively, is able to perform his duties very well and is able to take responsibility for what he does, has plans for his future. The purpose of this study was to obtain a self-confidence profile of MTs Al Bidayah students, while the method used was descriptive quantitative research method. With the questionnaire questionnaire data collection method to obtain a self-confidence profile of MTs Al Bidayah students, where the research subjects were 120 active students of MTs Al Bidayah. The results obtained in this study were 18% of students with low self-confidence, 62% of students who had moderate levels of self-confidence, 20% of students who had high levels of self-confidence. Keywords: : low self-confidence, self-identity